Police Shootings in Canada: An Empirical Analysis and Call for Data - Simpson, Rylan (Crime & delinquency, 2024)
We analyzed police shootings in Canada (except Québec) between 2017 and 2019. Drawing upon media reports and information provided by police oversight agencies, we attempted to identify all incidents where on-duty police officers discharged their firearm with the intent to strike a person. Findings indicated that such incidents occurred an average of 58 times per year. Approximately 39% of police shootings were fatal, 48% were non-fatal, and 12% were non-injurious. Most occurred in public spaces and were initiated by civilian requests for police service, typically for crime-related reasons. We discuss our findings with respect to both research and practice. We also call for official, incident-level data regarding police shootings to address concerns that otherwise exist about these incidents among civilians, practitioners, researchers, and policymakers.